(untitled) - Trucco, Emilce; Bernasconi, Pablo; Tirado, Gabriel; Astesiano, Alfredo (Universidad Nacional de Cuyo. Facultad de Ciencias Médicas)

Pericarditis constrictiva (2009)

(untitled)
Fil: Trucco, Emilce. Hospital Español de Mendoza. Departamento de Cardiología.